Friendly Education: Prophet Muhammad's Interactions with Children - Nasirudin, Nasirudin; Musthofa, Musthofa; Kunaepi, Aang (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
Acts of violence, both verbal and non-verbal, that threaten children often occur in interactions between adults and children. Acts of violence like this are very counterproductive in the world of education. This article aims to analyze how the Prophet PBUH interacted with kids who had their universe. Following that, a descriptive analysis was conducted on the hadiths about the Prophet's contact with children that were recorded in the hadith books. Child-friendly education is a concept that emphasizes the importance of fostering a sense of safety and enjoyment in children. The Prophet's interactions with children provide valuable guidelines for child-friendly education. He greets them with a sense of security, appreciates their unique world, and allows them to play without scolding. He encourages sadness by joking with them and does not discriminate against children based on gender. This child-friendly educational model deserves further research to identify more comprehensive and in-depth prophetic education methods. The Prophet's affectionate approach towards children makes him a valuable model for educators.